Studi Perubahan Kandungan Histamin Ikan Lemuru (Sardinella lemuru) Pada Kondisi Suhu Ruang/Terbuka - Wafi Ayodhya Satyadharma; Ima Yudha Perwira; I Wayan Darya Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2022)
Examination the quality of freshness of fish is important to increase the level of fish consumption (protein consumption) of Indonesian society. If the handling is not correct, the protein contained in fish will be used by microorganisms to reproduce and reduce the quality of the fish and the formation of histamine content. The purpose of this study is to determine the histamine content in sardine fish and the relationship between the histamine content in sardine fish that were left at room temperature. This research is conducted by taking sardine fish samples at PPN Kedonganan, then leaving them on a 2 hour time scale. After settling the sardine fish, the histamine content testing using the ELISA method. Histamine content in sardines (Sardinella lemuru) left for 2 hours ranges from 3.1-39.9 ppm, histamine content in sardines (Sardinella lemuru) which is left for 4 hours ranges from 30,0-40,5 ppm, and histamine content in sardines (Sardinella lemuru) which were left for 6 hours ranged from 42.1-100 ppm.The increase in histamine content in sardine fish (Sardinella lemuru) can be affected by room temperature, the longer the sardine fish is left at room temperature, the histamine content in sardine fish can increase.